2003
DOI: 10.1046/j.1365-3040.2003.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological localization of blue light sensory sites in etiolated dicotyledon seedlings

Abstract: Changes induced by blue light (BL) in ion fluxes and pH in etiolated seedlings of dicotyledons ( Cucumis sativus L., Phaseolus lunatus L., Pisum sativum L.) were studied using a non-invasive ion-selective microelectrode technique (MIFE). BL induced significant Ca 2 + uptake within the first 5 min after onset in upper parts of the whole cucumber seedling. To locate the sites of the BL perception, studies on excised segments were performed. The data obtained demonstrated that the observed Ca 2 + uptake is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The overall changes lasted less than 100 s. However, a single blue-light pulse desensitized the system to subsequent pulses and recovery took place over 3-4 h, not unlike the dark recovery to a strict localization of PHOT1::GFP at the plasma membrane reported in the present study. Two groups have reported blue-light-induced increases in calcium uptake by etiolated tissues of Arabidopsis (Stoelzle et al, 2003) and several other dicot species (Babourina et al, 2003), respectively. Stoelzle et al (2003) found the response strongly reduced in a phot1-5 mutant and completely absent in a phot1-5 phot2-1 double mutant.…”
Section: Phot1::gfp Subcellular Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall changes lasted less than 100 s. However, a single blue-light pulse desensitized the system to subsequent pulses and recovery took place over 3-4 h, not unlike the dark recovery to a strict localization of PHOT1::GFP at the plasma membrane reported in the present study. Two groups have reported blue-light-induced increases in calcium uptake by etiolated tissues of Arabidopsis (Stoelzle et al, 2003) and several other dicot species (Babourina et al, 2003), respectively. Stoelzle et al (2003) found the response strongly reduced in a phot1-5 mutant and completely absent in a phot1-5 phot2-1 double mutant.…”
Section: Phot1::gfp Subcellular Distributionmentioning
confidence: 99%
“…RPT2 (a member of the same protein family as NPH3) is required both for phototropism and stomatal opening, but not for chloroplast relocation (Inada et al, 2004). In addition, cytoplasmic concentrations of Ca 2+ , K + , Na + , Cl -, and H + can change during phototropinmediated blue-light signaling, indicating that changes in some ion channels and/or pumps are mediated by phototropins (Babourina et al, 2003;Baum et al, 1999;Fuchs et al, 2003;Harada et al, 2003;Stoelzle et al, 2003). Recent studies indicate that phot1 plays a role in drought tolerance in Arabidopsis (Galen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…) and the localisation of BL receptors (Babourina et al . ) in a range of plant species, as well as for revealing the association between light‐induced transient ion fluxes and leaf growth and photosynthesis (Shabala & Newman ; Shabala & Hariadi ; Živanović et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten-millimetre-long segments from the upper part of the epicotyl a few millimetres below the apical hook were then harvested. Harvested material was fixed vertically in plastic holders in measuring chambers as described previously (Babourina et al 2003). Chambers were filled with the measuring solution (0.2 mM KCl, 0.1 mM CaCl 2 , pH 5.5) to approximately 5 mm above the upper cut surface of the stem.…”
Section: Measurement Of Ion Fluxes During Phototropic Inductionmentioning
confidence: 99%